Upaya Meningkatkan Etika Komunikasi Remaja dengan Teman Sebaya melalui Bimbingan Kelompok di Panti Asuhan Hanifa Jorong 3 Kampung Nagari Gadut Tilatang Kamang Kabupaten Agam - Aprilia, Aisyah Bunga; Syawaluddin, Syawaluddin (MASALIQ, 2023)
Speaking is a form of communication tool used by individuals besides writing and listening. The communication that is carried out, of course, aims to convey messages to one individual to another. Communication is a necessity which of course cannot be separated from human life. In conveying a message, of course not everyone has the same ethical way of conveying messages properly. The research approach used in this research is qualitative. Where this method uses interview and observation methods in describing efforts to improve the ethics of communication between adolescents and peers. The purpose of the observations in this study was to see how the methods and ethics of communication used by adolescents in daily activities with peers. Many teenagers often ignore good communication ethics, especially with peers. This is due to environmental factors and individual innate which results in the neglect of ethics that must be maintained in communication.